Fico porque quero ou porque preciso? Um estudo sobre o entrincheiramento organizacional - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The term organizational understands the idea of withdrawal be tied to an organization for not believing that there are other options that will support according to your expectations and needs. You can be interpreted as the organization being a circle of protection, security, stability, guarantee sustenance of its status quo and escape of other damage linked to its shutdown. This study aimed to analyze the different levels of entrenchment of financial institutions employees ' organizational of Santana do Livramento, Rio Grande do Sul, Brazil. The study was characterized as descriptive exploratory, with quantitative approach applied to 40 employees of financial institutions, including credit unions, private and public banks. The main results showed that Social Position Adjustment dimensions and Limitations of alternatives, have a medium degree of entrenchment, and the Bureaucratic Arrangements Impersonal dimension showed a higher incidence, being an influential factor of the construct. You can see a degree of entrenchment and thus appears to be space to explore further the theme, deepening especially questions about the possible positive or negative effects of entrenchment, both in other banking organizations and organizations of other natures.

El término “afianzamiento organizacional” está estrechamente relacionado a una organización, debido a que no existen otras opciones que apoyarán o proveerán para sus expectativas y necesidades. Se lo puede interpretar como una organización siendo un círculo de protección, seguridad, estabilidad, garantía de sostenimiento de su status quo y escape de otros daños vinculados a su cierre. Este estudio pretende analizar los diferentes niveles de afianzamiento de los empleados de las instituciones financieras organizacionales de Santana do Livramento, Rio Grande do Sul, Brasil. El estudio es de carácter descriptivo exploratorio, con enfoque cuantitativo aplicado a 40 empleados de instituciones financieras, incluyendo cooperativas de ahorro y crédito, bancos públicos y privados. Los principales resultados mostraron que las dimensiones de ajuste de posición social y las limitaciones de las alternativas, tienen un grado medio de atrincheramiento, y la dimensión burocrática impersonal de arreglos demostró una mayor incidencia, siendo un factor influyente de la construcción. Se puede ver un grado de enquistamiento, siendo así un motivo para explorar más el tema, profundizando especialmente en preguntas sobre los posibles efectos positivos o negativos de afianzamiento, tanto en otras entidades bancarias como en organizaciones de otras naturalezas
I'm staying because i want or because i need? A study on the organizational entrenchment
Me quedo porque quiero o porque necesito? Un estudio sobre el fortalecimiento organizacional
Keywords: Entrincheiramento organizacional; Instituições financeiras; Bancários; Organizational entrenchment; Financial institution; Banking; Fortalecimiento organizacional; Instituciones financieras; La banca; CNPQ::CIENCIAS SOCIAIS APLICADAS